2002
DOI: 10.1002/art.10316
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐La/SSB antibodies transported across the placenta bind apoptotic cells in fetal organs targeted in neonatal lupus

Abstract: Objective. To determine whether La and/or Ro epitopes on apoptotic cells in fetal organs that are targeted in neonatal lupus syndrome (NLS) are accessible for binding by autoantibodies in vivo, we traced the fate of transplacental autoantibodies in a murine passive transfer model.Methods. Pregnant mice at day 15 of gestation (E15) were injected intraperitoneally with human antiRo/La-positive sera or control sera, and transplacental transfer of human autoantibodies was tested by enzymelinked immunosorbent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 28 publications
4
39
0
3
Order By: Relevance
“…Similar to other NLS manifestation rhizomelic chondrodysplasia punctata occurs as a result of IgG-apoptotic cell complexes presented in the zones of newly forming fetal bones initiating an immune complex-mediated inflammation at growth plates [12].…”
Section: Musculoskeletal Manifestationsmentioning
confidence: 76%
See 1 more Smart Citation
“…Similar to other NLS manifestation rhizomelic chondrodysplasia punctata occurs as a result of IgG-apoptotic cell complexes presented in the zones of newly forming fetal bones initiating an immune complex-mediated inflammation at growth plates [12].…”
Section: Musculoskeletal Manifestationsmentioning
confidence: 76%
“…Maternal autoantibodies mediate fetal autoimmune disease through formation of antibody complexes with apoptotic antigens in the skin, liver, heart and newly forming bone which when phagocytosed and opsonized initiate proinflammatory process that results in immune-mediated damage to fetal tissues [12,13].…”
Section: Pathogenesismentioning
confidence: 99%
“…[70] [17] [69] [74] Systemic lupus erythematosus (SLE) The pathogenesis of SLE is strongly associated with C1q deficiency, it has been demonstrated that C1q does not bind apoptotic cells isolated from SLE patients. The pathogenic role of the complement in SLE is still unclear, but it seems to be linked to impairment of apoptotic cell removal.…”
Section: Mechanismmentioning
confidence: 99%
“…Although La is a relatively low abundance protein sequestered primarily in cell nuclei, it is likely to be accessible to autoreactive lymphocytes under certain circumstances, such as apoptosis of cells (13,33,34), since hLa peptides appear to be constitutively presented by B cells in hLa Tg mice (7). Despite this Ag exposure, splenic autoreactive hLa-specific B cells were not deleted in hLa ϫ anti-hLa double-Tg mice, but instead were present in numbers equivalent to those of naive hLa-specific B cells from single-Tg anti-hLa littermates.…”
Section: Autoreactive Hla-specific B Cells Mature and Populate The Pementioning
confidence: 99%